IMPLEMENTASI KEBIJAKAN ALIH FUNGSI LAHAN RESAPAN AIR MENJADI PEMUKIMAN DI KAWASAN BANDUNG UTARA (Kelurahan Cipageran Dan Kelurahan Citeureup) - , Noer Apptika Fujilestari; Atik Rochaeni; Mafrihatul Khasanah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research needs to be carried out to find out how policy implementation occurs in the North Bandung area, especially in Cipageran Village and Citeureup Village, where in practice so far, the implementation of policies related to land conversion is not always in line with what has been planned with there still being a large amount of land being converted. but it is not in accordance with the Cimahi City regional spatial plan. Referring to Cimahi City Regional Regulation Number 4 of 2013 concerning Cimahi City Regional Spatial Planning for 2012-2032, the essence of this regional regulation is regarding the direction of spatial use in the North Bandung area, including protected areas and cultivation areas. The research method used in this research is a qualitative approach with descriptive research methods. The results of research on the implementation of the policy on changing the function of water catchment land, starting from policy planning and operational implementation, have been carried out in accordance with the regulations, but the facts on the ground show that the implementation of policies related to land use change has not been effective. So the policy to control the conversion of water catchment land in the Cipageran Village and Citeureup Village areas is very difficult to implement, but the government continues to take various actions as a preventive measure by providing strict implementation of the rules and strictness of the sanctions given.